A CROSS-SECTIONAL STUDY EVALUATION OF DIAGNOSTIC IMPLICATIONS OF PLATELET INDICES IN THROMBOCYTOPENIA. - Nayak, Jayanti; Behera, Bodhisatwa; Mohanty, Saroj Ranjan Mohanty; Patro, Manoj Kumar; Singh, Kiran; Meher, Lalit Kumar (Student’s Journal of Health Research Africa, 2023)
Introduction: Thrombocytopenia (TCP) refers to a reduction of platelet count below 150 x 109/ L; it’s not a disease entity by itself, but a finding that may result from a number of disease processes. Automated hematology analyzers that determine the Mean Platelet Volume (MPV), Platelet Distribution Width (PDW), Plateletcrit (PCT), and Platelet Large Cell Ratio (P-LCR), could be very helpful to facilitate the differential diagnosis of thrombocytopenia and to monitor thrombocytopenic conditions. Materials and methods: A cross-sectional study of platelet indices of 512 thrombocytopenic samples by automated hematology analyzers was done. Results: The cases of thrombocytopenia were classified into hypo-productive (362 cases) and hyper-destructive (150) groups. A most common cause of hypo-productive and hyper-destructive thrombocytopenia was Aplastic anemia and ITP, respectively. All the indices were significantly higher (p-value < 0.05) in hyper-destructive TCP compared to hypo-productive TCP, except Plateletcrit. Conclusion: The results of the present study show platelet indices to be a useful and reliable test to differentiate between hyper-destructive thrombocytopenia from the hypo-productive type with statistically significant differences.